PENERAPAN TEKNOLOGI INFORMASI DI LAYANAN PERPUSTAKAAN UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG - Ilhami , Ilhami; Putri, Erin Dwi; Mariana, Mariana; Salsabilla, Maulia Ananda (LP2M Universitas Bina Bangsa, 2025)
Information Technology Based Library Services at the UIN Raden Intan Lampung Library include circulation services, reading rooms, references, information browsing and internet access. The aim is to improve the quality of service to users. The UIN library has implemented IT-based services with the Simpus automation program, so that services are faster and more accurate. This has a positive impact on users and librarians, and makes the librarian's task easier in serving users. Library reference services continue to develop thanks to technology. This research evaluates the impact of information technology on library reference services in Asia and identifies features that are currently in use. This research method is a qualitative approach through literature study by collecting data from the library website at UIN Raden Intan Lampung which uses the Ask Librarian service.